Fewer Levels of Dedicated Trauma Care Leads to Better Outcomes. Issue 5 (May 2023) - Thacker, Christopher; Nealon, Kathleen; Torres, Denise; Leonard, Dianne; Young, Katelyn; Rapp, Megan
Background: Dedicated trauma intensive care units (ICUs) staffed by surgical intensivists lead to better patient outcomes. Increased length of stay (LOS) leads to worse outcomes. Little research has focused on the effect of dedicated trauma medical-surgical units or ICU/medicalsurgical systems. In 2018, our Level 1 trauma center transitioned from 3 non-dedicated levels of care (ICU/stepdown unit/medical-surgical) to 2 dedicated levels of care (ICU/medical-surgical). Our objective was to look at patient outcomes pre- and post-intervention. Methods: Retrospective analysis of trauma registry data was performed on patients (age ≥18) admitted to the trauma service at a Level 1 rural trauma center over 46-months. In the pre-intervention group, step down and medical-surgical patients were combined as "Non-ICU" for analysis. Standard statistical analysis was performed. Results: Analysis included 6103 patients. The group demographics were similar, except pre-intervention patients had higher ISS and fewer comorbidities. Emergency department LOS decreased from 30 versus 13.9% ( P < .0001) and 15.9 versus 5.8% ( P < .0001) for greater than 3 and 6 hours, respectively. Median LOS decreased for all patients ( P < .0001). Mortality dropped from 9.0 versus 5.5% ( P = .0009) for ICU and 1.7 versus 0.26% ( P = .0013) for non-ICU patients. Overall patient mortality was level at 3.7%. Inpatient complications dropped from 9.9 versus 8.5% ( P = .07). Unplanned ICU readmissions were unchanged ( P = .4169). For patients with 3+ comorbidities, overall LOS dropped by 2 days ( P < .0001) and home discharge increased from 42.8 versus 51% ( P < .0001). Conclusion: Implementation of 2 levels of dedicated care has decreased ED and hospital LOS for all trauma patients without increasing mortality or complications. Patients with extensive comorbidities saw the most improvements.